2017
DOI: 10.18632/oncotarget.23734
|View full text |Cite
|
Sign up to set email alerts
|

The vascular disrupting agent combretastatin A-4 phosphate causes prolonged elevation of proteins involved in heme flux and function in resistant tumor cells

Abstract: Vascular disrupting agents (VDAs) represent a promising class of anti-cancer drugs for solid tumor treatment. Here, we aim to better understand the mechanisms underlying tumor reccurrence and treatment resistance following the administration of a VDA, combretastatin A-4 phosphate (CA4P). Firstly, we used photoacoustic tomography to noninvasively map the effect of CA4P on blood oxygen levels throughout subcutaneous non-small cell lung cancer (NSCLC) tumors in mice. We found that the oxygenation of peripheral tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 56 publications
3
38
0
Order By: Relevance
“…Hemoproteins and enzymes that are required for OXPHOS are also protumorigenic. Interestingly, a recent study from the authors' lab showed that viable NSCLC tumor cells resistant to the vascular disrupting agent, combretastatin A-4 phosphate, exhibit further elevated levels of hemoproteins and proteins and enzymes involved in heme metabolism (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemoproteins and enzymes that are required for OXPHOS are also protumorigenic. Interestingly, a recent study from the authors' lab showed that viable NSCLC tumor cells resistant to the vascular disrupting agent, combretastatin A-4 phosphate, exhibit further elevated levels of hemoproteins and proteins and enzymes involved in heme metabolism (32).…”
Section: Discussionmentioning
confidence: 99%
“…IHC was carried out exactly as described previously (32). Paraffin-embedded tumor tissues from mice described above were used.…”
Section: Ihcmentioning
confidence: 99%
“…In 4 animals, both tumors could not be visualized in a single imaging slice, resulting in 4 tumors being excluded, leaving 12 tumors for analysis. Combretastatin 4A phosphate (CA4P, C7744; Sigma-Aldrich), a potent Vascular Disrupting Agent with well-established efficacy in preclinical models, was used (30,41,42). When tumors reached approximately 8 mm linear dimension, mice were randomly allocated into two groups: treated (CA4P, 8 mL/kg of 12.5 mg/mL solution dosed intraperitoneally to achieve a dose of 100 mg/kg, n ¼ 7 tumors, 4 mice) and vehicle (PBS 8 mL/kg intraperitoneally, n ¼ 5 tumors, 4 mice).…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Imaging studies were performed both before and 4 hours after administration of the vascular disrupting agent combretastatin A4 phosphate. The 4-hour time point was chosen so as to observe the induced vascular disruption prior to the development of substantial tumor necrosis (30).…”
Section: Oe-ot and Dce-ot Are Highly Sensitive To Treatment With A Vamentioning
confidence: 99%
See 1 more Smart Citation